Novel Insights into Pressure‐Sensitive Adhesives Based on Plant Oils. Issue 15 (11th June 2015) - Maaßen, Wiebke; Oelmann, Stefan; Peter, David; Oswald, Walter; Willenbacher, Norbert; Meier, Michael A. R.
<x xml:space="preserve">Abstract</x> This work investigates the synthesis of bio‐based pressure‐sensitive adhesives and their characterization in terms of mechanical properties relevant to processing and application. The synthesis of monomers based on various fatty acids derived from vegetable oils as renewable feedstock via a one‐step, a two‐step, and a three‐step route is described. The resulting monomers are polymerized via free radical polymerization resulting in high molecular weight polymers with adhesive properties. Adhesives are also obtained as aqueous dispersions by means of miniemulsion polymerization. In particular, the monomer acrylated methyl oleate (4ac) and the thereof derived polymer are intensively studied. The synthesized homopolymers show characteristic mechanical and adhesive properties similar to conventional pressure sensitive adhesives.